Decisões técnico-musicais e interpretativas no Segundo Caderno de Poesilúdios para piano de Almeida Prado - Junia Canton Rocha (2004)
This research focus on the second book of Almeida Prados Poesilúdios for solo piano from a pianistic perspective, regarding both technique and language. This research also work with the extra musical images that inspired the composer, either from the indications found in the score or the composer himself, in order to obtain a better insight on the sets musical conception. I propose my own technical and musical ideas regarding practicing strategies as possible ways to lead to effective interpretative decisions. One of the main goals of this study is to contribute for a better knowledge of Almeida Prado and his second book of Poesilúdios, by looking at it from the pianists perspective during the preparation and interpretation of the musical work.